The fatty acid composition of Estonian and Latvian retail milk; implications for human nutrition compared with a designer milk. Issue 2 (22nd May 2018) - Henno, Merike; Ariko, Tiia; Kaart, Tanel; Kuusik, Sirje; Ling, Katri; Kass, Marko; Jaakson, Hanno; Leming, Ragnar; Givens, D Ian; Sterna, Vita; Ots, Meelis
Abstract : The study reported in this Research Communication compared retail milks' FA profiles from two neighbouring countries, estimated the potential contributions of these milks and a designer milk (achieved by changing the diet of the dairy cow) to the recommended human dietary intake of FA, and predicted (based on the milk FA profile) methane emission from dairy cows. Retail milks in Estonia and Latvia were purchased from supermarkets monthly for one year. To compare the FA composition of retail milk with designer milk with an increased PUFA content, the bulk milk FA profile from a separate field trial was used. Milk FA concentrations of the two neighbouring countries were affected by state, season and their interaction, while the main influence on all these factors were different feeding practices (grazing availability, forage to concentrate ratio and legume-rich silages vs. maize silages). Three cups (600 mL; fat content 2·5 g/100 g) of Estonian, or Latvian retail milk or designer milk per day contributed more to the recommended intakes of saturated FA (SFA) (42·5, 42·7, 38·7%, respectively) than other FA. Compared to the retail milks, α-linolenic acid estimated intake was almost doubled by designer milk consumption (19·7% of adequate intake) without influencing summed intakes of SFA and trans FA. There were state and seasonal differences in the predicted methane outputs of dairy cattle based on retail milk FA. Although the FA profiles of retail milks in the two neighbouring countries were affected by state and season, an appreciable increase in human dietary intakes of beneficial fatty acids from milk, and concomitant reduction in methane emissions from dairy cows, can be achieved only by targeted feeding.